Development and evaluation of eco-friendly biopesticides against aphids and pod borer of food legumes in Morocco - Boulamtat, Rachid; Kemal, Seid Ahmed (International Center for Agricultural Research in the Dry Areas, 2023)
Temperate food legumes (faba bean, chickpea, field pea and lentil) are important food and feed crops in West Asia, north and East Africa regions. The productivity of legume crops is affected by Aphids (Acyrthosiphon pisum and Aphis fabae) and pod borer (Helicoverpa armigera). Due to climate and farming systems changes, the impacts of insect pests are increasing, and farmers are discouraged from including food legumes in their cropping systems. Besides direct economic damage, many aphid species play important roles as vectors of legume viruses like Pea seed-borne mosaic virus. Sources of resistance to aphids and pod borers are not available in temperate food legume gene-pool and farmers use insecticides to protect their crops. Looking for biopesticides as a component of biorational pest management against aphids and pod borers is a major area of research for development to increase productivity and production and of food legumes in Morocco.